An integrated approach to new food product development (CRC Press, 2009)
New products often fail not because they are bad products, but because they don't meet consumer expectations or are poorly marketed. In other cases, the marketing is spot on, but the product itself does not perform. These failures drive home the need to understand the market and the consumer in order to deliver a product which fulfills the two equally important goals of consumer trial and repeat purchase. The linkage of these issues is often compromised in the "innovate or die" world of corporate new products. An Integrated Approach to New Food Product Development explores this inter-relationship and the inter-relationship of the key disciplines essential for marketplace success.